Clinical Characteristics and Histopathology of Coronavirus Disease 2019-Related Deaths in African Children. Issue 9 (15th June 2021) - Mabena, Fikile C.; Baillie, Vicky L.; Hale, Martin J.; Thwala, Bukiwe N.; Mthembu, Nonhlanhla; Els, Toyah; Serafin, Natali; du Plessis, Jeanine; Swart, Peter; Velaphi, Sithembiso C.; Petersen, Karen L.; Wadula, Jeannette; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Globally, very few childhood deaths have been attributed to coronavirus disease 2019 (COVID-19). We evaluated clinical, microbiologic and postmortem histopathologic findings in childhood deaths in whom severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was identified antemortem or postmortem. Methods: Surveillance of childhood deaths was ongoing during the initial COVID-19 outbreak in South Africa from April 14, 2020, to August 31, 2020. All children hospitalized during this time had a SARS-CoV-2 test done as part of standard of care. Postmortem sampling included minimally invasive tissue sampling (MITS) of lung, liver and heart tissue; blood and lung samples for bacterial culture and molecular detection of viruses (including SARS-CoV-2) and bacteria. The cause of death attribution was undertaken by a multidisciplinary team and reported using World Health Organization framework for cause of death attribution. Results: SARS-CoV-2 was identified on antemortem and/or postmortem sampling in 11.7% (20/171) of deceased children, including 13.2% (12/91) in whom MITS was done. Eighteen (90%) of 20 deaths with SARS-CoV-2 infection were <12 months age. COVID-19 was attributed in the causal pathway to death in 91.7% (11/12) and 87.5% (7/8) cases with and without MITS, respectively. Lung histopathologic features in COVID-19–related deaths included diffuse alveolar damage (n = 6, 54.5%), type 2 pneumocyte proliferation (n = 6, 54.5%) and hyaline membrane formation (n = 5, 36.4%). Culture-confirmed invasive bacterial disease was evident in 54.5% (6/11) of COVID-19 attributed deaths investigated with MITS. Conclusions: COVID-19 was in the causal pathway of 10.5% (18/171) of all childhood deaths under surveillance. The postmortem histopathologic features in fatal COVID-19 cases in children were consistent with reports on COVID-19 deaths in adults; although there was a high prevalence of invasive bacterial disease in the children.